Environmental effects of ozone depletion and its interactions with climate change: progress report, 2009 - Andrady, A.; Aucamp, P.; Bais, A.; Ballare, C.; Bjorn, L.; Bornman, Janet; Caldwell, M.; Cullen, A.; Erickson, D.; de Gruijl, F.; Hader, D.; Ilyas, M.; et al. (Royal Society of Chemistry, 2010)
The parties to the Montreal Protocol are informed by three panels of experts. One of these is theEnvironmental Effects Assessment Panel (EEAP), which deals with UV radiation and its effects onhuman health, animals, plants, biogeochemistry, air quality and materials. Since 2000, the analyses andinterpretation of these effects have included interactions between UV radiation and global climatechange. When considering the effects of climate change, it has become clear that processes resulting inchanges in stratospheric ozone are more complex than believed previously. As a result of this, humanhealth and environmental problems will likely be longer-lasting and more regionally variable. Like theother panels, the EEAP produces a detailed report every four years; the most recent was that for 2006(Photochem. Photobiol. Sci., 2007, 6, 201–332). In the years in between, the EEAP produces a lessdetailed and shorter progress report,